Revitalisasi Kesenian Rudat Sindang - Majida, Andi Zulfa; Chusna, Adrini Amalia; Lutfiati, Arfia; Anam, Mohammad Kaerul; Pangestu, Muhamad Aji; Sufyan, Muhamad Faza Aryansah; Adawiyah, Robiatul; Safitri, Siti Indri Ainun; Aisyah, Siti Kharisma Nurul; Latifah, Siti; Sugiarti (Profetik: Jurnal Pengabdian Masyarakat, 2024)
Rudat sindang art is a local cultural heritage only owned by Sindang Village Dukuhwaru District Tegal Regency is currently facing challenges existential and requires real efforts to restore it. This dedication explores efforts to save this art through the application of an Aset-Based Community Development (ABCD) inthe context of activities Community Service (PKM). The main focus of PKM this is a book on Rudat dance art, which includes complete documentation of songs and dance movements traditional. The ABCD approach is used to identify and mobilize community assets that can contribute to saving the art of Rudat Sindang. Analysis a (Asset) highlighting the potential of local artists’ expertise, knowledge traditional, and community support as the main aset. Through Analysis B (Building), collaboration is formed between government, cultural institutions, and society, to building a strong foundation for this rescue effort. Bookkeeping of Rudat dance art has bocome a concrete product of  PKM activities. Complete documentation about songs and Rudat dance movements not only function as an important archive, but also as an educational tool that can be accessed by wide community. By involving the community in the process bookkeeping, these efforts also strengthen social engagement in preserving traditional arts. It is hoped that the results of this activity will provide guidance practical for local communities and related parties in preparing strategy to save Rudat Sindang art. As a product it is hoped that the bookkeeping of Rudat dance arts will be concrete play a key role in strengthening cultural identity, preserving traditional heritage, and creating continuity in the practice of Rudat Sindang dance.